Estudio de factibilidad para la creación de una empresa especializada en el servicio de catering y el desarrollo de eventos sociales en la ciudad de Quito - Pérez Lara, Edison Roberto (2013)
The service "Quito Catering". Search enter the market of services, so that through this work the feasibility for Creating a Specialized Catering Service Development focused Social Events in the City of Quito Company will be studied.